O CARISMATISMO NAS CEBS E O DECLÍNIO DE SUAS UTOPIAS POLÍTICAS. UM ESTUDO DA IGREJA CATÓLICA EM DIADEMA E SÃO BERNARDO DO CAMPO (1980-2007) - Ramos, Nólia Mendonça de Novaes (2008)
This dissertation aims at studying the decline of the political utopias of the Ecclesial Base Communities of the Roman Catholic Church in the cities of Diadema and São Bernardo do Campo, in Sao Paulo, Brazil, in period 1980-2007. In order to do so, it will analyze the Catholic Church in the Region of the Great ABC Of São Paulo in the period of the Military Dictatorship, the change of the political religious field in the end of the decade of 70 of last century, and the constitution of syndicalism in the Great ABC, with the same Utopian ideals of the Theology of Liberation that were substantiating Communities Ecclesial s discourse and practices. We observe from the Decade of 80 a process that we called charismatization of communities, characterizing of a new profile in the militancy, or still a period of changes in the initial Utopias of the movement, which start to have more individualists practices.(AU)